Perception of dental students and graduates on the community practices carried out during their professional training (Revista Nacional de Odontología, 2025)
Community practices allow the integration of concepts, the identification of problems and the participation in joint decisions to offer comprehensive care to patients, families and communities; they are carried out in real scenarios to foster engagement with the community and enable direct observation for the analysis of health-related problems. A qualitative research study was conducted using a phenomenological method. Eighteen participants, including students and graduates, took part in the study. Data were collected through a single-session focus group. The main results identified four categories of analysis: experiences, strengths, contributions and difficulties among students and graduates. It is concluded that community practices during dental education provide significant benefits by strengthening professional training and interpersonal skills, while promoting a community-oriented approach and the advancement of public health.
Keywords: Public Health; Health Education; Practice